Enhanced External Counterpulsation - A Review - Sayami, LA; Ullah, M; Rahman, MT; Rahman, Z; Roy, D; Majumder, AAS (Cardiovascular Journal, 2010)
DOI: 10.3329/cardio.v2i2.6647 Cardiovasc. j. 2010; 2(2) : 236-244